THE EFFECTIVENESS OF STIMULER APPLICATION IN IMPROVING STUDENTS’ ENGLISH SPEAKING SKILL AT MA NWDI KETANGGA - Pebianti, Kuspina; Yulia Agustina; Siti Ayu Surayya; Siti Maysuroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
English speaking skill is essential yet challenging for EFL learners due to linguistic barriers and psychological constraints. This study aims to empirically investigate the effectiveness of the Stimuler Application as a learning medium in improving students' English speaking skills. Employing a quantitative true experimental design, specifically a pre-test and post-test control group design, this research involved 36 eleventh-grade students at MA NWDI Ketangga, divided equally into an experimental class and a control class. Data were collected through a speaking test assessing pronunciation, fluency, vocabulary, grammar, and comprehension, and subsequently analyzed using the Mann-Whitney U test. The results revealed a highly significant difference in speaking performance between the two groups (U = 0.0, Sig. < 0.001). The experimental class achieved a massive post-test mean score of 90.44, significantly outperforming the control class's mean of 71.56, with the most prominent improvements observed in the aspects of fluency and pronunciation. In conclusion, the Stimuler Application is highly effective in accelerating oral proficiency by providing high-frequency independent practice and immediate AI-driven diagnostic feedback, thereby successfully reducing speech hesitation and lowering the students' affective filter.